Pengaruh NaCl dan Waktu Perendaman Terhadap Asam Oksalat dan Mutu Tepung Porang - Marthen Saubaki; Agrippina A. Bele; Marlon D. G. Wola; Hidayah Usman (Animal Agricultura, 2026)
Porang tuber (Amorphophallus muelleri) has potential as a functional food ingredient; however, its utilization is limited by the high oxalate content, which acts as an irritant and antinutritional compound. This study aimed to analyze the effects of NaCl concentration and soaking time on the reduction of oxalate content and on the color and aroma quality of porang flour. The experiment was arranged in a factorial Completely Randomized Design with NaCl concentrations of 0, 5, 10, and 15% and soaking times of 0, 30, 60, and 90 minutes. Porang tubers were sliced, soaked, dried, and milled into flour. Oxalate content was determined using permanganometric titration, while sensory quality was evaluated organoleptically. The results showed that increasing NaCl concentration and soaking time significantly reduced oxalate content. The 15% NaCl treatment for 90 minutes produced the highest oxalate reduction while maintaining acceptable color and aroma quality.